Assessment of Learning Climate in Nepalese Banking Sectors - Parajuli, Suman Kamal; Aryal, Sujan (Journal of Advanced Research in HR and Organizational Management, 2023)
Organizational performance and creativity have been connected to learning organizations. Successful organization will be able to stay up with changes and advancements in the business environment by learning. Base on this statement study examined Nepal’s public and private banking sectors’ learning atmosphere. This study was objectivity, cross sectional base in nature. 250 structure questionnaires were distributed, among that 210 Managerial level employee reply the questionnaire. Mean and std. deviation was used to measure the perception of employee towards learning organization, reward and motivation. Result reveled that Organizational learning environments were found to be average 3.1716 in both the public and private sectors of the financial industry, Reward system to foster learning organization in the banking industry seems like regular 3.5286, employee motivation in learning organizations, appears average 3.5469. The average opinion of Nepal’s learning environment among employees of public and private banking sectors was conclusion. How to cite this article: Parajuli SK, Aryal S. Assessment of Learning Climate in Nepalese Banking Sectors. J Adv Res HR Organ Mgmt 2023; 10(1): 1-6. DOI: https://doi.org/10.24321/2454.3268.202301